1989
DOI: 10.1096/fasebj.3.2.2521610
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase 24.11 (enkephalinase) and related regulators of peptide hormones 1

Abstract: This report summarizes the recent rapid development of research on neutral endopeptidase 24.11 (enkephalinase; NEP) and on two other metalloenzymes, meprin and endopeptidase 24.15. NEP cleaves a variety of active peptides, including enkephalins, at the amino side of hydrophobic amino acids. The cDNA for human, rat, and rabbit NEP has been cloned and the deduced protein sequences revealed a high degree of homology (93-94%). Site-directed mutagenesis proved that an active site glutamic acid is involved in cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
314
1
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(329 citation statements)
references
References 1 publication
4
314
1
10
Order By: Relevance
“…[25][26][27][28] NEP also contributes to the degradation of extracellular BK (specially when ACE is inhibited). 29 In human cardiac tissue, NEP accounts for nearly 50% of the metabolism of BK.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] NEP also contributes to the degradation of extracellular BK (specially when ACE is inhibited). 29 In human cardiac tissue, NEP accounts for nearly 50% of the metabolism of BK.…”
Section: Discussionmentioning
confidence: 99%
“…NEP has been implicated in the metabolism and regulation of a variety of biologically active peptides, e.g. the enkephalins, substance P, atrial natriuretic factor, bradykinin and the chemotactic peptide fMet-Leu-Phe [7,8]. The amino acid sequence of human NEP is identical with that of the common acute lymphoblastic leukemia antigen (CALLA; CD 10) and is highly conserved in different species [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of active peptides are known to be NEP substrates in vitro (Erdös and Skidgel, 1989). It has been shown that NEP regulates the biological activity of the peptide substrates in vivo by modulating their local concentrations available for receptor bind- Immunohistochemical staining of NEP/CD10 in gestational choriocarcinoma tissues.…”
Section: Ino Et Almentioning
confidence: 99%
“…However, the enzyme is also expressed on a variety of nonhematopoietic cells and certain solid tumor cell lines (Chu and Arber, 2000). Because NEP cleaves small peptides on the aminoterminal side of hydrophobic amino acids, there are many known NEP substrates including enkephalins, atrial natriuretic factor, substance P, bombesin, and endothelins (Erdös and Skidgel, 1989). The physiological role of the enzyme depends on available substrates in specific organs and cell types (Shipp and Look, 1993).…”
mentioning
confidence: 99%